Therapeutic Patient Education and Eating Habits: A Challenge in Caries Disease - Marjorie Zanini; Mélodie Clerc; Sylvie Azogui-Levy; Annabelle Tenenbaum (Dentistry Journal)
Dietary Factors and Oral Health: Risky dietary behaviors, particularly excessive sugar consumption, significantly contribute to dental caries. Dental practitioners are tasked with detecting and managing these behaviors to effectively treat caries and prevent recurrences. Although dietary assessment tools exist to identify such behaviors, they have limits. Furthermore, traditional methods, focused on information dissemination and advice, often fall short in promoting sustainable changes in patient behavior toward oral health. From our perspective, there is a necessity to integrate educational approaches with therapeutic management for enhancing the ability current and future dental practitioners to effectively care for their patients’ oral health needs. Discussion: Specific educational models have been developed for patients with chronic diseases, through Therapeutic Patient Education (TPE), defined as helping patients acquire or maintain the skills they need to best manage their lives with a chronic disease. Future Directions: By incorporating TPE into dental practice, oral health professionals can empower patients to take control of their eating habits and reduce their risk of caries disease. This holistic approach addresses both the carious lesions and underlying causes of tooth decay, leading to better oral health outcomes for patients.